Alcohol Intoxication and Its Influence on the Course of Male Rats Spermatogenesis - Nelia Dolynko; Tetiana Mykytyn; Natalia Bielova (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
Morphometric and functional analysis of germ cells in histological micropreparations and ejaculate of male rats at the control group on the 7th, 14th, 21st and 28th days of alcoholization at experimental animals was performed. Prolonged use of ethanol has been shown to reduce resistance to spermatogenic epithelial cells, which are at different stages of development, manifested by inhibition of spermatogenesis with a decrease in sperm count and spermatids, and in ejaculate - a decrease in sperm concentration with increasing number of spermatozoa.